Russo-EU relations : impact of the navalny factor - Cheang, Chris (2021)
The EU announced on 2 March 2021 new sanctions against Russia over the imprisonment of Alexei Navalny, the opposition figure. This development only confirms the already tense Russo-EU relationship but will not lead to a point of no return.